ECOLOGIA TRÓFICA DE Pyrrhulina australis (LEBIASINIDAE) NA BACIA DO RIO IVINHEMA, ALTO RIO PARANÁ - VIEIRA, Anna Carolina Souza; SÚAREZ, Yzel Rondon; LIMA- JUNIOR, Sidnei Eduardo (ANAIS DO ENIC, 2025)
-